The Consumption of Fresh Vegetables from Street Food and Sanitation of Street Stalls at Four Locations in Bogor City - Utami, Donna Fujie Rahaditha; Rahayu, Winiati P; Nuraida, Lilis (UI Scholars Hub, 2019)
The consumption of fresh vegetables at the stalls needs serious attention. This research aimed to estimate the exposure probability due to fresh vegetables consumption of street food consumers, to measure sanitation level of street stalls that serving fresh vegetables, and to recommend a mentoring program for the stalls at four locations in Bogor City. This research was conducted at 16 stalls located at four locations in Bogor City. The number of respondents surveyed was 293 people and determined by stratified sampling method. Food frequency questionnaire was used as a tool in the survey. The survey showed that men consumed more fresh vegetables than women with the average of 47.12 g/person/consumption and frequency 3.37 times/week (p<0.05). Adults consumed fresh vegetables at the stalls most often with 3.05 times/week and the average consumption of 44.59 g/person/consumption (p<0.05). All street stalls were at level IV of sanitary practices. Thus, there is a risk of food safety in consuming fresh vegetables at the stalls at four locations in Bogor City. Men and adults had high exposure probability to microbiological hazards due to fresh vegetables consumption at the stalls. Mentoring program for all locations involving socialization and implementation of street stall management and sanitation practices regulations by government, full awareness of street vendors in complying with the prevailing regulations, and firm action for the vendors who violate the rules.